1995
DOI: 10.1113/jphysiol.1995.sp021091
|View full text |Cite
|
Sign up to set email alerts
|

Activation of nicotinic acetylcholine receptors increases the rate of fusion of cultured human myoblasts.

Abstract: 1. Fusion of myogenic cells is important for muscle growth and repair. The aim of this study was to examine the possible involvement of nicotinic acetylcholine receptors (nAChR) in the fusion process of myoblasts derived from postnatal human satellite cells. 2. Acetylcholine‐activated currents (ACh currents) were characterized in pure preparations of freshly isolated satellite cells, proliferating myoblasts, myoblasts triggered to fuse and myotubes, using whole‐cell and single‐channel voltage clamp recordings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 44 publications
3
66
1
Order By: Relevance
“…A modest rectification in current-voltage relation for human muscle γ-AChR channels has been previously observed in native preparations (27,28).…”
Section: Discussionmentioning
confidence: 56%
“…A modest rectification in current-voltage relation for human muscle γ-AChR channels has been previously observed in native preparations (27,28).…”
Section: Discussionmentioning
confidence: 56%
“…These latter cells are myoblasts cultured at low density in the differentiation medium for 2-3 days. In these conditions, myoblasts are induced to proceed through the steps preceding fusion but, as they cannot contact neighboring cells, they remain mononucleated (16). ] i similar to that of undifferentiated myoblasts (65 Ϯ 14 nM, n ϭ 393); the remaining 20% have a significantly (P Ͻ 0.001) increased resting [Ca 2ϩ ] i (105 Ϯ 21 nM, n ϭ 98).…”
Section: Resultsmentioning
confidence: 99%
“…Krause et al (9) observed a large up-regulation of ACh receptor density in cultured human myoblasts when they were switched from proliferative to differentiating growth conditions, but before fusion to myotubes. Our results are comparable to theirs in that we recorded large ACh receptor currents from nonfused uninucleate cells which had been growing in conditions that induce differentiation, again indicating that ACh receptor induction, like IRK up-regulation, is well underway prior to fusion.…”
Section: Discussionmentioning
confidence: 99%